Nutrition and Degenerative Brain Dysfunctions - Bell, V.; Fernandes, T. H. (European Journal of Applied Sciences, 2023)
The aim of the present mini review is to describe the nutritional role on the onset of brain neurodegenerative pathologies, some of genetic origin, others transferred from animals to humans. An outline is given on some pathophysiological mechanisms and nutrition with emphasis on nucleotide nutrition and mushrooms as foods or supplements on retarding ageing and preventing neurodegenerative diseases. Prions, prionoids and protein misfolding disorders are described as responsible for several neurodegenerative proteinopathies. Mention is made on cellular proteostasis network and translocation of proteins from the cytosol across membranes, scrutinised by molecular chaperones such as heat shock proteins, associated with cellular homeostasis in the critical regulation of neural physiological function. Some mechanisms preventing the formation of non-functional proteins relevant to neural physiological states and implications of cellular stress responses to human physiology and diseases are referred. The genetic regulation of protein synthesis plays an important role as transcriptional control in the regulation of gene expression being necessary to identify the molecular biomarkers and the misfolded proteins relevant to neural functions. It is evident that dietary nutrition aids in the prevention and remediation of neurologic symptoms and food components play an important role on the early prevention against neurodegenerative diseases while specific nutrients and nucleotides are considered essential for normal immune defences. A brief consideration is made on the microbiota-gut-brain axis signalling the interference and maintenance of homeostasis and brain physiology. Our previous research showed the potential for mushrooms to target neurogenesis through several bioactive compounds able to counteract neurodegenerative brain disorders.